Case report: A 53-year-old woman with synchronous WHO classification II and IV gliomas - Jia, Fang; Kang, Yin; Wang, Zhanxiang (Frontiers in Oncology, 2024)
Introduction: Glioma is the most common primary intracranial neoplasm with a relatively poor prognosis.Here, we present a unique case of a 53-year-old woman with two histopathologically distinct gliomas at the initial diagnosis. She presented with headaches and left limb weakness before admission, and magnetic resonance imaging (MRI) showed right frontal and basal ganglia area involvement combined with hemorrhage. The patient underwent a navigation-guided craniotomy for tumor removal. Pathological examination revealed the right frontal lobe lesion as a WHO grade II IDH-NOS astrocytoma, but the right parietal lobe lesion was a WHO grade IV IDH-mutant diffuse astrocytoma. Molecular detection of the parietal lesion revealed a point mutation at the R132 locus of the IDH1 gene, no mutation in the TERT promoter, amplification of the epidermal growth factor receptor, and a non-homozygous CDKN2A/B deletion. Discussion: In-depth epigenomic analysis and molecular examination revealed that one patient had two different brain tumors, underscoring the importance of performing a comprehensive brain tumor workup. Conclusion: This unique case confirms that adjacent astrocytomas may have different molecular pathogenesis and provides novel insights into the development of gliomas.